Laparoscopic management of perforated appendicitis-a study of 90 cases (Journal of Surgical Sciences, 2020)
Introduction: Acute appendicitis is the most common general surgical emergency in the world. It may cause potential risk for patients due to its life threaten complications like burst (perforation). The perforated appendicitis often leads to serious infectious complication like abdominal sepsis, pelvic abscess & etc. There are concerns of using laparoscopic appendectomy to perforated appendicitis. Now a days laparoscopic management of perforated appendicitis is the standard surgical option in many countries. Laparoscopic procedure has tremendous advantages over the open procedure regarding its diagnosis, exclusion of additional pathology, surgical treatment, wound infection (port infection), hospital stay & overall patient’s satisfaction. The aim of this prospective study was to evaluate the role and application of laparoscopy in the management of complicated appendicitis (perforation).Methods: It is a prospective study conducting during January 2011 to May 2019 in BSMMU and some private hospitals of Dhaka, Bangladesh. It includes 90 patients in whom laparoscopic appendicectomy & peritoneal lavage was performed. Three ports technique were usual. Sometimes 4th port is required. 10 mm port is telescopic port. The other one is 3/5 mm port and another one is 5/10 mm port.Energy source is unipolar diathermy. Intracorporeal knotting, endoloop and haemoclip are used for haemostosis& ligating appendicular stump.Results: Age distribution of the study is 3-90 years, mean 17 years. Male is predominant. Duration varies 10-120 minutes, mean 70 minutes. Duration varies 30-120 minutes, mean 70 minutes. Hospital stay varies from 48-96 hours, mean 64 hours. There were 8 complications- single (5, 5.55%) or multiple (3, 3.33%) port infections, paralytic ileus (2, 2.22%) and diarrhea (1, 1.11%), port TB was identified (3, 3.33%) cases among the port infection. Conversion was 1 (1.11%) for controlling haemorrhage of burst appendicitis. All complications are managed conservatively.Conclusion: Total management of perforated appendicitis by laparoscopy is excellent. So it is achievable, feasible & can be done by expert hand in any center. Now it is considered as standard procedure.Journal of Surgical Sciences (2019) Vol. 23(2): 59-66